Analgesic use, parents' clan, and coffee intake are three independent risk factors of chronic kidney disease in middle and elderly-aged population: a community-based study. (April 2014) - Hsu, Yung-Chien; Lee, Pei-Hsien; Lei, Chen-Chou; Shih, Ya-Hsueh; Lin, Chun-Liang
Abstract Chronic kidney disease (CKD) is a world-wide public health problem. The purpose of this study was to identify the role of some controversial potential risk factors in development of CKD. "Community Complex Health Screening" is a large-scale, free, health program for individuals ≥40 years of age that has been available since January 2002 in Chiayi County, Taiwan. A questionnaire was administered to study participants, collecting information on ethnicity, use of analgesics, and life habits. Age, sex, and blood biochemical analyses were considered as potential confounders. A high prevalence and low awareness of CKD were noted in this population. Females with CKD had a lower awareness of their illness than males. Analgesic users had a significantly lower estimated glomerular filtration rate (eGFR). Age (OR = 1.095), females (OR = 0.348), fasting plasma glucose (OR = 1.005), level of uric acid (UA) (OR = 1.517), and analgesic usage (OR = 1.512) remained independent predictors of CKD. Multivariate linear regression found that use of analgesics, father' clan from Fujian, mother' clan from Fujian, and coffee intake were independent determinants of renal outcome with coefficient of regression (β) of −0.102, −0.192, 0.210 and 0.88, respectively. The prevalence of CKD decreased with advanced education. Further, there was no significant difference between education background and analgesics use. In conclusion, analgesic use, parents' clan, and coffee intake were independent risk factors for CKD in middle-aged and elderly Taiwanese. Thus, an effective educational program that increases the awareness of such individuals residing in rural counties is warranted.